Does Copyright Enforcement Encourage Piracy? - Rick Harbaugh; Rahul Khemka (Claremont McKenna College, Department of Economics, 2000)
More intensive copyright enforcement reduces piracy, raises prices, and lowers consumer surplus. We show that these results do not hold regarding the extent rather than intensity of enforcement. When enforcement is targeted at high-value buyers such as corporate and government users, the copyright holder has an incentive to charge super-monopoly prices, thereby encouraging piracy among low-value buyers. Extending enforcement down the demand curve broadens the copyright holder's captive market, leading to lower prices and higher sales that can increase both profits and consumer surplus. The standard tradeoff between the incentive to generate intellectual property and the cost of monopoly power is therefore avoided. Private enforcement by copyright holders may be insuciently extensive since consumers can also benefit from more extensive enforcement. Similarly, new technologies which lead to stronger control over illicit use can paradoxically benefit consumers.
Keywords: K11; K42; L86; L43; D42; 330; piracy; internet; intellectual property; copyright protection; super-monopoly pricing